Improving the Quality of Educational Services Through the Utilization of Learning Resources and the Effectiveness of Teacher Performance: Peningkatan Mutu Layanan Pendidikan Melalui Pemanfaatna Sumber Belajar dan Efektivitas Kinerja Guru - Rahman, Novianti Azizah (Medpro, 2025)
The purpose of this study was to analyze the influence of learning resource utilization and teacher effectiveness on the quality of educational services in elementary schools. The study was conducted using a quantitative descriptive method, involving 47 teachers from Cakrabuana Elementary School Cluster IV, Talun District, Cirebon Regency. Data were collected through questionnaires, observations, and interviews, and analyzed using descriptive statistical techniques, Pearson correlation, and multiple linear regression. The results showed that learning resource utilization had a significant relationship with the quality of educational services (r = 0.663), as did teacher effectiveness (r = 0.752). Simultaneously, both contributed 69.1% to the quality of educational services (R² = 0.691; F = 49.313; p < 0.05). These findings indicate that the success of basic education delivery is largely determined by the extent to which teachers are able to utilize available learning resources and carry out their roles professionally and effectively. The implications of this study emphasize the importance of developing teacher capacity and the availability of learning resources that support innovative learning as an integral part of efforts to continuously improve the quality of basic education services.